IEEE Radiation Effects Data Workshop
DOI: 10.1109/redw.2002.1045543
|View full text |Cite
|
Sign up to set email alerts
|

Total dose bias dependency and ELDRS effects in bipolar linear devices

Abstract: Total dose tests of several bipolar linear devices show sensitivity to both dose rate and bias during exposure. All devices exhibited Enhanced Low Dose Rate Sensitivity (ELDRS). An accelerated ELDRS test method for three different devices demonstrate results similar to tests at low dose rate. Behavior and critical parameters from these tests are compared and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The detailed test results for two device types, LM139 and LM124, that were particularly sensitive to dose rate effects are presented in Figure 1 and Figure 2. As expected from previous reports [1][2][3][4][5][6], many devices exhibited some degree of sensitivity to dose rate effects. In most of cases, however, this sensitivity was not significant enough to have major practical impact for many typical spacecraft applications.…”
Section: Methodssupporting
confidence: 85%
“…The detailed test results for two device types, LM139 and LM124, that were particularly sensitive to dose rate effects are presented in Figure 1 and Figure 2. As expected from previous reports [1][2][3][4][5][6], many devices exhibited some degree of sensitivity to dose rate effects. In most of cases, however, this sensitivity was not significant enough to have major practical impact for many typical spacecraft applications.…”
Section: Methodssupporting
confidence: 85%
“…Such a result is not surprising since the mechanisms at play at LDR and HDR are not the same [15]. Similar results were also reported in the literature [9][10][11], showing that experimental dose sensitivity evaluation should be performed using the bias conditions corresponding to the on-flight application.…”
Section: Bias Effect On Dose Rate Responsesupporting
confidence: 85%
“…Although it is generally assumed that irradiation with all pins grounded corresponds to the worst case, it has been shown that this is not always the case [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the enhanced low dose rate sensitivity (ELDRS), which results in enhanced degradation of bipolar linear integrated circuits when irradiated at low dose rates, has been reported extensively in Refs. [1][2][3]. In addition, testing of some linear voltage regulators shows that they exhibit both an ELDRS effect and bias dependency OE1 4 , but there is little in the literature that discusses the relation between biases and the ELDRS effect.…”
Section: Introductionmentioning
confidence: 99%